2007
DOI: 10.1007/978-3-540-38448-9
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Calculations

Abstract: Techniques to compute absolute free energies of classical many-body systems are discussed with special emphasis on those techniques that can be used to map the phase diagram of solids and liquids. Recent technical advances in the study of multi-component systems and systems consisting of flexible molecules are emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…This implies that the molecules, if they are free to rotate in place, could lower their energy by aligning with the electric field of the cavity mode, which could possibly lead to self-organization (for the example system above, this also requires breaking of the overall spherical symmetry). The details of this effect depend on the precise setup, such as the cavity material and shape, molecular and solvent properties, etc., and would require a more complete treatment taking thermodynamical effects and free energy into account [111,112], which is beyond the scope of the current work. However, we mention that it has recently been shown that strong coupling and the associated formation of polaritons itself could lead to alignment due to the associated decrease of the lower polariton energy, provided that a significant fraction of molecules are excited to lower polariton states [29,113].…”
Section: Collective Effectsmentioning
confidence: 99%
“…This implies that the molecules, if they are free to rotate in place, could lower their energy by aligning with the electric field of the cavity mode, which could possibly lead to self-organization (for the example system above, this also requires breaking of the overall spherical symmetry). The details of this effect depend on the precise setup, such as the cavity material and shape, molecular and solvent properties, etc., and would require a more complete treatment taking thermodynamical effects and free energy into account [111,112], which is beyond the scope of the current work. However, we mention that it has recently been shown that strong coupling and the associated formation of polaritons itself could lead to alignment due to the associated decrease of the lower polariton energy, provided that a significant fraction of molecules are excited to lower polariton states [29,113].…”
Section: Collective Effectsmentioning
confidence: 99%
“…Functional uncertainty quantification (FUQ) can, in principle, be used to assess the uncertainties originating from approximate input constitutive laws, correct predictions if a more accurate function becomes available, and rank when and where to replace a low-fidelity model used in a simulation with one of higher fidelity in order to reduce prediction error by running additional simulations. This paper introduces a computationally efficient method to compute FDs in MD simulations involving two-body interatomic potentials, extending ideas from thermodynamic integration and free-energy perturbation methods [21,22]. The FD quantifies how a quantity of interest (QoI) -in this case the total potential energy or pressure computed from an MD simulation in the canonical ensemble -depends on the input function, here the Lennard-Jones (LJ) two-body pair potential.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is very hard to calculate the absolute free energy of real systems because we don’t know their partition functions. Free energy calculations allow us to bypass this problem, but require at least two states: a reference state whose free energy can be analytically or numerically found, and a final state of interest 36, 37 . We chose to calculate the free energy difference using alchemical free energy calculations, a method in which we simulate a series of non-physical intermediates between the end states 38 .…”
Section: Theorymentioning
confidence: 99%